The addition effect of fermented Aegle marmelos fruit and bamboo shoots in cattle feces slurry to the reduction of ammonia gas emission - Fitriyanto, Nanung Agus; Waluyo, Ramai Tri; Erwanto, Yuny (2016)
This study aimed to determine the effect of fermented Aegle marmelos and bamboo shoots in reducing ammonia gas emission from cattle feces slurry. Aegle marmelos, bamboo shoots, molasses, and water were fermented for 10 days in anaerobic condition. The fermentation product was then investigated for chemical properties, sensory aspects, microbial content as well as the growth on the solid and liquid medium by measurement the optical density (OD600nm), and the concentration of ammonia gas emission. The study was performed by added at different level 0% (control), 1%, 3%, 5% of fermentation product and 1% of commercial starter EM-4 into cattle feces slurry to observe the ability of ammonia gas emission reduction. The data of fermentation product such as physical and chemical properties, sensory, and the growth of microbes from fermentation product on the solid and liquid medium, the optical density (OD600nm), and microbial growth after the treatment were descriptively analyzed. Ammonia gas concentration was analyzed with Factorial Complete Randomized Design Patterns (5x4) when it showed significant differences; the analysis will be followed by Duncan's New Multiple Range Test (DMRT). The results of the study showed that the fermentation product has the pH: 3.05, temperature 26°C, the color is brown to black, fresh scent, slightly sour, fragrant. Microbial fermentation observation results showed that it could be grown on a solid medium and liquid. The addition of fermentation product has significantly decreased (P <0.01) to the ammonia gas emission.